The role of social networks in bank lending - Oliver Rehbein; Simon Rother (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
This paper analyzes social connectedness as an information channel in bank lending. We move beyond the inefficient lending between peers in exclusive networks by exploiting Facebook data that reflect social ties within the U.S. population. After accounting for physical and cultural distances, social connectedness increases cross-county lending, especially when lending requires more information and screening incentives are intact. On average, a standard-deviation increase in social connectedness increases cross-county lending by 24.5%, which offsets the lending barrier posed by 600 miles between borrower and lender. While the ex-ante risk of a loan is unrelated to social connectedness, borrowers from well-connected counties cause smaller losses if they default. Borrowers' counties tend to profit from their social proximity to bank lending, as GDP growth and employment increase with social proximity. Our results reveal the important role of social connectedness in bank lending, partly explain the large effects of physical distance, and suggest implications for antitrust policies.
Keywords: D82; D83; G21; O16; L14; Z13; 330; bank lending; social networks; information frictions; distance; culture